Stress and anxiety among mothers of premature infants in a Malaysian neonatal intensive care unit - Ong, Swee Leong; Abdullah, Khatijah Lim; Danaee, Mahmoud; Soh, Kim Lam; Soh, Kim Geok; Japar, Salimah (Taylor & Francis, 2019)
Objective: This study aims to determine maternal stress and anxiety as perceived by mothers whose premature infants were admitted to the neonatal intensive care unit (NICU) and to identify maternal stress and its relationship with maternal and infant characteristics and anxiety. Background: Vulnerable premature infants commonly require special care in the NICUs. In most cases, prolonged hospitalization results in stress and anxiety for the mothers. Methods: A non-probability convenience survey was used in a public hospital, with 180 mothers completing the 26-item Perceived Stress Scale (PSS) and a 40-item State-Trait Anxiety Inventory (STAI). Results: 56.5% of mothers had high levels of stress, 85.5% of mothers had a high level of state-anxiety and 67.8% of mothers had a high level of trait-anxiety. The stress experienced by these mothers had a significant relationship with anxiety, and was found to be associated with state and trait anxiety levels, but not with maternal and infant characteristics. Conclusion: Mothers in this setting revealed high levels of stress and anxiety during their premature infants’ NICU admission. An immediate interventional programme focusing on relieving mothers’ anxiety and stress is needed to prevent maternal stress and anxiety at an early stage. © 2018, © 2018 Society for Reproductive and Infant Psychology.